Efektivitas Pemberdayaan Masyarakat dalam Pengelolaan Komoditas Sagu - Antonius M. K Letsoin; Rulinawaty Rulinawaty; Muhammad Sawir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the clarity of objectives, achievement strategies, planning, and preparation, as well as facilities and infrastructure prepared to support the community empowerment program in managing the sago commodity in Obaa District, Mappi Regency which is to be achieved. This type of research is qualitative research. Data analysis in this research used the N-vivo software tool. The results of research, programs, and strategies for community empowerment through sago processing aim to eradicate poverty, empowerment planning is an action to meet food needs and planning actions to increase community and regional income, preparation of a community empowerment program in managing sago commodities in Obaa District, Mappi Regency is a program design sago as food for the Mappi community and sago as a source of income for the Mappi community and area, the facilities and infrastructure provided are 7 units of sago production house, 1 unit of packing warehouse, 5 units of sago dewatering machines, 6 dismal machines (floating machines), 6 press machines sago, 9 units of chain saw machines, 1 unit of 3-wheeled vehicle, 2 units of Viber 15 PK boats, 5 units of permanent sago grating machines while there are 13 units of potable ones. Conclusions, objectives, achievement strategies, planning, preparation, as well as facilities and infrastructure prepared to support the community empowerment program in managing the sago commodity in the Obaa District, Mappi Regency, which are to be achieved have been well planned. Keywords: Effectiveness, Community Empowerment, Sago Commodity